LolA and LolB from the plant-pathogen Xanthomonas campestris forms a stable heterodimeric complex in the absence of lipoprotein - Furlanetto, Valentina; Divne, Christina (Frontiers in Microbiology, 2023)
The Gram-negative bacterium Xanthomonas campestris is one of the most problematic phytopathogens, and especially the pathovar campestris (Xcc) that causes a devastating plant disease known as black rot and it is of considerable interest to understand the molecular mechanisms that enable virulence and pathogenicity. Gram-negative bacteria depend on lipoproteins (LPs) that serve many important functions including control of cell shape and integrity, biogenesis of the outer membrane (OM) and establishment of transport pathways across the periplasm. The LPs are localized to the OM where they are attached via a lipid anchor by a process known as the localization of lipoprotein (Lol) pathway. Once a lipid anchor has been synthesized on the nascent LP, the Lol pathway is initiated by a membrane-bound ABC transporter that extracts the lipid anchor of the LP from the IM. The ABC extractor presents the extracted LP to the transport protein LolA, which binds the anchor and thereby shields it from the hydrophilic periplasmic milieu. It is assumed that LolA then carries the LP across the periplasm to the OM. At the periplasmic face of the OM, the LP cargo is delivered to LolB, which completes the Lol pathway by inserting the LP anchor in the inner leaflet of the outer membrane. Earlier studies have shown that loss of Xcc LolA or LolB leads to decreased virulence and pathogenicity during plant infection, which motivates studies to better understand the Lol system in Xcc. In this study, we report the first experimental structure of a complex between LolA and LolB. The crystal structure reveals a stable LolA-LolB complex in the absence of LP. The structural integrity of the LP-free complex is safeguarded by specific protein-protein interactions that do not coincide with interactions predicted to participate in lipid binding. The results allow us to identify structural determinants that enable Xcc LolA to dock with LolB and initiate LP transfer.